Maternal weight status and the composition of the human milk microbiome: A scoping review. - Katherine Daiy; Victoria Harries; Kate Nyhan; Urszula M Marcinkowska (PLoS ONE)
The human milk microbiome is thought to partly contribute to the assembly of the infant gut microbiome, a microbial community with important implications for infant health and development. While obesity has well-established links with the adult gut microbiome, less is known about how it affects the human milk microbiome. In this scoping review, we synthesize the current literature on the microbial composition of human milk by maternal weight status, defined broadly as BMI (prepregnancy and postpartum) and gestational weight gain (GWG). This study followed the a priori protocol published in Prospero (registration #: CRD42020165633). We searched the following databases for studies reporting maternal weight status and a characterization of milk microbiota through culture-dependent and culture-independent methods: MEDLINE, Embase, Web of Science, CINAHL, and Scopus. After screening 6,365 studies, we found 20 longitudinal and cross-sectional studies investigating associations between maternal weight status and the composition of the milk microbiome. While some studies reported no associations, many others reported that women with a pre-pregnancy or postpartum BMI characterized as overweight or obese, or with excessive GWG, had higher abundances of the genus Staphylococcus, lower Bifidobacterium abundance, and lower alpha diversity (within-sample diversity). This review suggests that maternal weight status is minorly associated with the composition of the milk microbiome in various ways. We offer potential explanations for these findings, as well as suggestions for future research.